Creative Economic Development As An Attraction Of The Natar Hot Springs - Seli Agustiara; Ulil Albab; Mawardi Mawardi (Universitas Pahlawan Tuanku Tambusai, 2023)
The creative economy is a part of the service sector experiencing rapid development, marked by the emergence of numerous new forms of creativity. This research aims to understand the development and community participation in the creative economy in Natar tourism. The research was conducted using a qualitative descriptive research method. The population consists of the community in the village of Natar. Data was collected through observation, interviews and documentation. The research findings indicate that the development of hot spring tourism to the creative economy has yet to be effective due to the poor organization of vending locations and the lack of enhancement in the quality of the creative economy community. This situation reduced the attraction and interest of visitors, decreasing community participation in vending activities at the Natar Hot Spring tourist attraction. Additionally, there is a need for professional empowerment initiated by the government to amplify the existing potential, such as creating a unique brand for the Natar hot springs and marketing the outcomes of the creative economy beyond the region so that the income of participating community members is not solely dependent on the number of visitors.